2009
DOI: 10.1108/03074800910975188
|View full text |Cite
|
Sign up to set email alerts
|

Social software programs: student preferences of librarian use

Abstract: Purpose-The purpose of this paper is to present findings of an electronic survey to determine the extent of use of social software programs. Design/methodology/approach-The study was conducted to discover the extent to which students use social software programs, namely Facebook, MySpace, Instant Messaging and Second Life, and to determine their level of desire for having a librarian or library presence within those settings. A web survey was developed and distributed using convenience sampling. The survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Fernandez (2009) and Connell (2009), for example, caution libraries not to disregard privacy concerns, and Xia (2009), Bortree and Seltzer (2009), and Jo and Kim (2003) show the importance of active groups and frequent discussion in developing relationships with stakeholders. Graham et al (2009) found that Facebook could facilitate the development of professional relationships, but Epperson and Leffler (2009) did not find much enthusiasm with users about the link between SNSs and libraries.…”
Section: Reaching Out To Customersmentioning
confidence: 99%
“…Fernandez (2009) and Connell (2009), for example, caution libraries not to disregard privacy concerns, and Xia (2009), Bortree and Seltzer (2009), and Jo and Kim (2003) show the importance of active groups and frequent discussion in developing relationships with stakeholders. Graham et al (2009) found that Facebook could facilitate the development of professional relationships, but Epperson and Leffler (2009) did not find much enthusiasm with users about the link between SNSs and libraries.…”
Section: Reaching Out To Customersmentioning
confidence: 99%
“…While 25% of freshmen surveyed by Connell (2009) at Valparaiso University in Indiana "would not be friends with the library," 58% would accept a friend request from the library, and 17% would take the initiative to friend the library. A similar study by Epperson and Leffler (2009) showed that, while 70% of student Facebook users would not care about a librarian being on Facebook, 66% would be "friends" with the librarian (2009). It is not clear from Epperson and Leffler's data, however, whether the students would accept a librarian's friend request or would rather initiate the connection themselves.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The studies reported till so far Hendrix et al, 2009;Chu and Meulemans, 2008;Epperson and Leffler, 2009;Al-Daihani, 2010;Aharony, 2012;Gerolimos, 2011) were limited due to the libraries and librarians' low interest in social networking sites. In addition, the adoption of social networking sites by libraries and librarians was new as a concept and as such it was expected that the interest would be low.…”
Section: Conclusion Recommendations and Future Researchmentioning
confidence: 96%